U.S. Dental Students' and Faculty Members' Attitudes About Technology, Instructional Strategies, Student Diversity, and School Duration: A Comparative Study. Issue 4 (1st April 2014) - Abdelkarim, Ahmad; Benghuzzi, Hamed; Hamadain, Elgenaid; Tucci, Michelle; Ford, Timothy; Sullivan, Donna
Abstract : In this study, attitudes and perceptions of U.S. dental students and faculty members were evaluated regarding four aspects of dental education: technology integration, instructional strategies, student diversity, and school duration. A survey instrument with eight statements using a five‐point Likert scale and a free‐text comment section was developed and distributed through SurveyMonkey. A total of 426 students and 187 faculty members from ten U.S. dental schools participated, a response rate of 17 percent of those surveyed. Faculty and student responses were compared using the Mann‐Whitney U test. The results of this analytic procedure revealed that the groups differed in their average responses for seven of the eight statements. Analysis of the faculty and student comments revealed similar themes between the two groups. Both dental students and dental faculty members stated that technology integration should be viewed as only a supplement to conventional instruction and showed mixed opinions about electronic textbooks. Further, both groups had positive views of the roles of problem‐based learning, community service, and the integration of research practice into dental education. Both groups also valued diversity in the student body and supported the current four‐year duration of dental school.